Pain management: An ignored medical issue - Ranabir Pal; Swapan Kumar Paul; Pandurang Vithal Thatkar; Shrayan Pal (Wolters Kluwer Medknow Publications, 2016)
Background: Pain is reality from womb to tomb as the specific personalized articulated feeling of human beings whether they need respite or not. Objective: To find an optimum primary care approach to pain management. Methods: The investigators pursued a sincere effort to unearth an answer to pain management through their internalized clinical experience of managing the commonest presentation of symptoms at their clinics by hundreds of ailing citizens. Results: Since ancient times, thousands of interventions have been practiced for relief of pain including an array of self-medications and traditional practices. In the era of "Evidence Based Medicine" in this new millennium, all forms of pain managements need scientific evaluation by the application of highest research integrity before they can be adapted as a standard treatment protocol. As the severity of the pain is a grossly subjective, the treatment/drug of choice and/or the methods/dosage should depend on the judgments of objective severity by the health care providers, depending on the objective clinical/ radiological/ pathological/ biochemical criteria and if possible by formulating scoring systems. Rather than managing the pain based on the expressed perception of the severity of pain by the patient as mild, moderate or severe, we have to be innovative in the new paradigm of this nascent pain management scenario. Conclusions: We have to help the budding doctors to grow up not only as a sensible doctor, but also as a great human being, who will give due attention to pain through a holistic tailor-made approach.